Efficiency of Buzzing Bees in Fruit Set and Seed Set of Solanum violaceum in Sri Lanka. (22nd August 2012) - Wanigasekara, R. W. M. U. M.; Karunaratne, W. A. I. P.
Abstract : Plant-pollinator interactions are often considered as tightly coevolved, mutualistic relationships. The present study aimed at determining the flower visiting bees of the vegetable crop, Solanum violaceum, and the efficiency of buzz pollination by bees on fruit and seed production in Sri Lanka. Seven bee species: Hoplonomia westwoodi, Amegilla comberi, Patellapis kaluterae, Xylocopa tenuiscapa, Apis dorsata, Trigona iridipennis, and Ceratina hieroglyphica visited the flowers of S. violaceum, and the first four species were buzzing bees. Buzzing bees were the first to visit Solanum flowers and were followed by nonbuzzing bees. Handling time of H. westwoodi and P. kaluterae varied with the availability of pollen in anthers that deplete with the age of flower and stayed longer at new flowers than at old flowers. Handling time of the larger buzzing bee, H. westwoodi, was higher than that of the smaller P. kaluterae . The fruit set, seed set, and seed germinability in flowers visited by buzzing bees were significantly higher than those of the flowers bagged to exclude pollinators.